2021
DOI: 10.3390/biomedicines9060701
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Enhances Myocardial Mitophagy and Improves Cardiac Function via Irisin/FNDC5-PINK1/Parkin Pathway in MI Mice

Abstract: Myocardial infarction is the major cause of death in cardiovascular disease. In vitro and in vivo models are used to find the exercise mode which has the most significant effect on myocardial irisin/FNDC5 expression and illuminate the cardioprotective role and mechanisms of exercise-activated myocardial irisin/FNDC5-PINK1/Parkin-mediated mitophagy in myocardial infarction. The results indicated that expression of irisin/FNDC5 in myocardium could be up-regulated by different types of exercise and skeletal muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 72 publications
2
21
0
Order By: Relevance
“…However, the effects of different aerobic exercise modalities on cardiac mitophagy and cardiac function are significantly different and highly controversial (Chang & Ma, 2017). Our findings confirmed that both MICT and HIIT improved autophagic flux and mitophagy levels in mice with ischaemic and pressure‐overload HF, which was partially consistent with previous lesser evidence (Chang & Ma, 2017; Li et al., 2021; Ma et al., 2021; Moradi et al., 2019; Zhao et al., 2018). Note too that exercise‐induced mitophagy may differ from the conventional pathways, and studies have shown that PRKN played an indispensable role in exercise‐induced mitophagy initiation (Drake et al., 2019; Eiyama & Okamoto, 2015; Ni et al., 2015; Wu et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the effects of different aerobic exercise modalities on cardiac mitophagy and cardiac function are significantly different and highly controversial (Chang & Ma, 2017). Our findings confirmed that both MICT and HIIT improved autophagic flux and mitophagy levels in mice with ischaemic and pressure‐overload HF, which was partially consistent with previous lesser evidence (Chang & Ma, 2017; Li et al., 2021; Ma et al., 2021; Moradi et al., 2019; Zhao et al., 2018). Note too that exercise‐induced mitophagy may differ from the conventional pathways, and studies have shown that PRKN played an indispensable role in exercise‐induced mitophagy initiation (Drake et al., 2019; Eiyama & Okamoto, 2015; Ni et al., 2015; Wu et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, HIF1α in the myocardium of mice with both aetiologies of HF was also significantly reduced in the present study, which was consistent with the decreased HIF1α in the (Chang & Ma, 2017). Our findings confirmed that both MICT and HIIT improved autophagic flux and mitophagy levels in mice with ischaemic and pressure-overload HF, which was partially consistent with previous lesser evidence (Chang & Ma, 2017;Li et al, 2021;Ma et al, 2021;Moradi et al, 2019;Zhao et al, 2018).…”
Section: Exercises Differentially Facilitated Myocardial Mitophagysupporting
confidence: 93%
See 1 more Smart Citation
“…It is possible that the parameters of the exercise paradigm used in this study were not rigorous enough to exacerbate similar cardiovascular changes in PinK1 KO rats. There also is evidence that augmented mitochondrial function plays a role in exercise-related changes in mitophagy in cardiac tissue [73,74]…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Exercise is the main inducer of irisin secretion both in healthy and dysregulated metabolism individuals ( Huh et al, 2015 ). Studies have confirmed that exercise-induced irisin is correlated with improvement of cardiac function in general ( Seo et al, 2020 ), which partly by modulating autophagy and mitochondrial function ( Li et al, 2021a ; He et al, 2021 ). Further previous animal studies report that irisin is implicated in cerebrovascular protective effects of exercise by alleviating ischemic neuron injury ( Li et al, 2017 ; Lourenco et al, 2019 ).…”
Section: Introductionmentioning
confidence: 93%